Subarachnoid haemorrhage mimicking a STEMI. Issue 8 (1st December 2017) - Cima, Katharina; Grams, Astrid; Metzler, Bernhard
Abstract: A 50-year-old healthy woman presented with typical ECG findings of a ST elevation myocardial infarction, further to an abnormal anterior wall motion and elevated specific cardiac markers. A cerebral computed tomography scan revealed a subarachnoid and intraventricular haemorrhage due to a ruptured distal internal carotid aneurysm. The following report shows a rare case, in which subarachnoid haemorrhage mimics an acute ST elevation myocardial infarction.